Nazi Crimes in Poland. A Never-Ending Search for Justice (Contemporary Central & East European Law, 2020)
This article deals with the model for prosecuting Nazi crimes committed in Poland in the light of the model presently used in international criminal law. It tries to answer the question: should the investigation of crimes of international law be handed over to transnational tribunals? Should they be hybrid tribunals involving a national factor, or completely supra-national tribunals like the International Criminal Court? Is it legitimate to transfer jurisdiction over these matters to national courts? The case of unpunished Nazi crimes in Poland may give a partial answer to this question. Certainly, various attempts made after World War II, including procedures brought before Polish courts, have contributed to understanding the function of international criminal law, and finding the answer to the question of the best model for prosecuting crimes of international law. At present, we also have the experience of international criminal tribunals, in particular the ICC, which is an efficient machine for prosecuting crimes of international law. Interesting conclusions can be drawn from its functioning that could improve the work of Institute of National Remembrance (IPN) prosecutors, and shed new light on the considerations regarding the prosecution of Nazi crimes in Poland after World War II.